Malt gastric lymphoma regression in a renal transplant after conversion of immunosuppression to sirolimus - Lasmar, Euler Pace; Coelho, Luiz Gonzaga Vaz; Lasmar, Marcus Faria; Lasmar, Leonardo Faria; Nogueira, Adalberto Fernandes; Giordano, Luiz Flávio Couto; Vianna, Heloisa Reniers (Brazilian Journal of Transplantation, 2008)
B-cell non-Hodgkin lymphoma is the most common post-transplant lymphoproliferative disorder after solid organ transplantation and its treatment is not well defined. We report a case of gastric MALT lymphoma with fast, persistent, and complete remission after conversion of the immunosuppression from cyclosporine (CsA) to sirolimus (SRL). A 42-year-old woman was submitted to renal transplant in 1992 and had a evolution with no major abnormalities until 2006 when a gastroscopy performed to investigate dyspeptic symptoms showed a mixed MALT gastric lymphoma(with low and high grade components) associated with the presence of Helicobacter pylori(H. pylori) infection. Two therapeutic interventions in a one-week interval were carried out: treatment of the H. pylori infection (association of omeprazole, amoxicillin and clarithromycin for 14 days) and modification of the immunosuppression by substitution of CsA and azathioprine (AZA) by SRL. Control endoscopy performed one month later showed persistence of H. pylori infection and absence of gastric tumor. New endoscopies performed at two-month ,seven-month and one year after therapy confirmed the absence of neoplasia and H. pylori eradication. Currently, the patient has no complaints, with creatinine values of 1.8 mg/dl using SRL and ibersatan. SRL has been extensively studied as an anticancer drug, acting as inhibitor of mammalian target of rapamycin (mTOR) inhibitor. Accumulating data support mTOR’s role in lymphomagenesis. As far as we know, this is the first report of a gastric MALT lymphoma in a renal transplant patient that presented complete remission after alteration of the immunosuppression scheme with the introduction of SRL.